Description of the Application of Red Fruit Oil Ointment to Heal Grade 2 Diabetic Ulcers in Toyareka Village - Hidayanti, Antri; Julianto, Eko; Dyah Puspasari, Fida (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Background: Diabetic ulcers are one of the serious complications of diabetes mellitus that can lead to disability and amputation. Management of diabetic ulcers requires proper wound care to accelerate healing and prevent infection. One alternative used is red fruit oil ointment (pandanus conoideus oil), known to contain antioxidants and active compounds potentially accelerating wound healing. Objective: To describe the application of red fruit oil ointment in the healing of grade 2 diabetic ulcers in Toyareka Village, Kemangkon District, Purbalingga Regency. Method: This study used a case study method on one respondent with a grade 2 diabetic ulcer. Treatment was conducted over 14 days with application of red fruit oil ointment every two days. Data analysis in this case study was performed using a descriptive approach. Data were collected through interviews, direct wound observation and documentation of score using the Bates Jensen Wound Assessment Tool (BJWAT). Results: There was an improvement in wound healing, indicated by a decrease in the wound score from 44 to 28 after seven applications. This improvement was marked by increased tissue granulation, epithelization, reduce wound size, and enhanced tissue integrity. Conclusion: Application of red fruit oil ointment effectively accelerates the healing of grade 2 diabetic ulcers.